Pengaruh Literasi Keuangan, Perilaku Keuangan dan Toleransi Risiko Terhadap Keputusan Berinvestasi Mahasiswa Melalui Aplikasi Ajaib - Sulasih Sulasih; Wiwin Anjani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This study examines the influence of financial literacy, financial behavior, and risk tolerance on students’ investment decisions when using the Ajaib application. A quantitative research design was employed with a sample of 343 students who actively invest through the platform. Data were collected using a structured questionnaire and analyzed using Multiple Regression Analysis with IBM SPSS. The empirical results indicate that financial literacy and financial behavior both have a positive and significant influence on investment decisions. In contrast, risk tolerance shows a negative and significant effect, suggesting that students with lower tolerance for risk tend to adopt more cautious investment strategies. Furthermore, the three variables collectively demonstrate a significant simultaneous effect on investment decision-making. These findings highlight the importance of strengthening financial knowledge and responsible financial practices to enhance rational investment behavior, particularly among novice student investors using digital investment platforms.